Application of innovative apps in tourism - Sharun, D.; Gudaitienė, R.; Chebotarova, I. (ТОВ «Друкарня Мадрид», 2021)
During Covid-19 pandemic, an innovative method how to learn history of the city was developed as an alternative to traditional learning in the classroom. The aim of this method is to encourage young people to acquire knowledge related to urban history via innovative technologies. The article presents comparison of the innovative apps used for local tourism in the UK and Ukraine.
Keywords: classroom; tourism